(untitled) (Maharaja Surajmal Institute Law Journal, 2024)
Privacy is essential to a person’s identity. Experts in human behavior concur that people have an innate need for personal space and control over their private lives. This includes the right to manage personal information and live without undue interference. Protecting privacy is crucial as it fosters self-respect, independence, and the ability to make one’s own choices. Right to privacy evolved in broadly 6 stages, from right against the government to individuals right against society i.e individualistic approach towards privacy. In the beginning, India’s view of privacy was centered on a person’s liberty—their freedom from governmental interference. This is seen in seminal decisions where the court stressed the restrictions on government searches, such as M.P. Sharma v. Satish Chandra (1954). This early phase represents the freedom of a right-holder to operate without hindrance, and the state’s obligation to uphold individual autonomy in line with that freedom. The development of the internet and large-scale data collection methods drastically changed the privacy environment. People started to worry more and more about who could access and utilize their personal data and this change reflects in 2017’s Supreme Court judgement in Justice K.S. Puttaswamy (Retd.) & Anr. vs. Union of India & Ors ruled that the right to privacy is a fundamental right. It is inextricably linked to the right to life and to personal freedom guaranteed by Article 21 of the Indian Constitution. Dignity has inherent characteristics related to sexual orientation, family, marriage, and childbearing. They combine to create the privacy of a home. This ruling represents a step in the right direction: people now have more control over their data, and others (including businesses) are required to get permission and make sure the data is protected. Four basic legal connections are outlined by Hohfeld’s theory: power, privilege, liberty, and right. This research article uses this paradigm to apply to privacy rights in order to investigate how these rights have changed in terms of what people can do (liberty), what other people cannot do (right), what people can choose not to do (privilege), and what people can be prohibited from doing (power). We can better grasp how the legal foundation for privacy rights has changed and is still developing